The Effect of Variations in Fuel RON 92, RON 95 and RON 98 on Engine Performance with a Compression Ratio of 12.7:1 - Sulistyanto, Amin; Eka, Nanda; Herlambang, Erico Stefani (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the effect of using fuels with different octane ratings (RON 92, RON 95, and RON 98) on the performance of a 206 cc four-stroke gasoline engine with a compression ratio of 12.7:1. The benefits of this study are to provide technical references for vehicle owners, repair shops, and automotive manufacturers in selecting fuel that matches the engine's compression ratio, as well as to raise awareness of the importance of using high-quality fuel to maintain the performance, efficiency, and durability of modern vehicle engines. Testing was conducted using a dyno test method to measure power, torque, and specific fuel consumption (SFC) at various engine speeds. The test data were analyzed using a quantitative descriptive method, comparing engine performance parameters with each type of fuel. The test results showed that high-octane fuel, such as Pertamax Turbo (RON 98), produced the best performance, characterized by maximum power, highest torque, and optimal fuel efficiency. Conversely, the use of low-octane fuel caused knocking, incomplete combustion, and increased the risk of deposit formation and corrosion due to its higher sulfur content